The Severity of COVID-19 and Firm Market Value: How Does It Affect Firm? - Ananto Prabowo (The Indonesian Journal of Accounting Research, 2023)
This paper is prompted by the lack of relevant studies on the implication of dangerous infections of contagious diseases caused by Coronaviruses in firms in Indonesia. Therefore, the purpose of this study is to examine the effect of the severity of Covid-19 infection on the market value of firms. Research of the Covid-19 severity on firm market value is presented in this study based on quarterly information of Indonesian listed firms. By employing a generalized least squares approach, the study concluded that the severity of Covid-19 has resulted in a significant decline in the market value of firms in Indonesia. Further findings regarding cash holdings suggest that substantial cash reserves can mitigate the adverse effects of Covid-19 by acting as a cushion to absorb shocks. The outcomes of this research complement the prevailing literature on Covid-19 and the market value of firms and provide considerations for both theoretical and practical applications.